Benefit of a Short Chain Peptide as a Targeting Ligand of Nanocarriers for a Brain-Driven Purpose - Lo, Yu-Chen; Lin, Wen-Jen (Pharmaceutics, 2021)
Treatment of glioma remains a critical challenge worldwide, since the therapeutic effect is greatly hindered by poor transportation across the blood brain barrier (BBB) and low penetration into tumor cells. In this study, a peptide-conjugated nano-delivery system was explored for the purpose of glioma therapy. A peptide-decorated copolymer was used to prepare nanoparticles (NPs) by a solvent evaporation method. The particle size was in the range of 160.9 ± 3.3–173.5 ± 3.6 nm with monodistribution, and the zeta potentials ranged from −18.6 ± 1.2 to +7.9 ± 0.6 mV showing an increasing trend with R9-peptide. An in vitro cocultured BBB model illustrated the internalization of peptide-conjugated NPs in bEnd.3 cells followed by uptake by U87-MG cells indicating both BBB-crossing and glioma-penetrating abilities. IVIS (In Vivo Imaging System) images revealed that T7-conjugated NPs specifically accumulated in the brain more than peptide-free NPs and had less biodistribution in nontarget tissues than T7/R9 dual-peptide conjugated NPs. The benefit of T7-peptide as a targeting ligand for NPs across the BBB with accumulation in the brain was elucidated.